Updates on the genetic characterization of vitiligo - Al-Shobaili, Hani A. (International Journal of Health Sciences, 2011)
Summary: Vitiligo is an autoimmune skin disorder in which autoimmune-mediated destruction of melanocytes caused depigmentation of skin patches. The complex genetics of vitiligo involves multiple susceptibility loci, genetic heterogeneity and incomplete penetrance with gene-gene and gene-environment interactions. In order to clarify the genetic factors, two different principal approaches have applied for the identification of genomic regions or candidate genes that mediate susceptibility to vitiligo. First approach is the genome-wide linkage analyses, which is conducted by scanning of entire human genome for genomic regions that are linked to the development of vitiligo. The other approach is functional candidate gene association (FCGA) analyses that detect specific candidate genes, which are expected to involve in disease on the basis of their priori biological functions. Genomic-wide scans have provided a strong support for vitiligo susceptibility genes on chromosomes 4q13-q21, 1p31, 7q22, 8p12 and 17p13, while loci of interest at 6p, 6q, 14q, 9q, 13q, 19p and 22q required further follow-up. Whereas, FCGA studies have identified some candidate genes which are associated with vitiligo, such as HLA, AIRE, VIT1, CAT, FOXD3, ESR1, COMT, PTPN22, NALP1, PDGFRA, MYG1, MITF, CD117, XBP1, FAS, COX2, EDN1 and ACE, but few of them reports now appear to be false-positive. This review will provides an update on genetics of vitiligo based on the identification of novel candidate genes that represent, in my opinion as optimal utility for future therapeutic targets in the pathogenesis of vitiligo. Keywords: Vitiligo, genetics, novel candidate genes, melonocytes, genome. Abbreviations: HLA Human leukocyte antigen CTLA-4 Cytotoxic T lymphocyte-associated antigen 4 ACE Angiotensin-converting enzyme CAT Catalase PDGFRA platelet-derived growth factor receptor, alpha polypeptide PTPN22 Protein tyrosine phosphatase, non-receptor type 22 (lymphoid) MYG1 Melanocyte proliferating gene 1 MITF Microphthalmia- associated transcription factor CD117 Cluster of differentiation 117 ESR 1 Estrogen receptor 1 FOXD3 Forkhead box D3 AIRE The autoimmune regulator COMT Catechol O-methyl transferase XBP1 X box binding protein 1 EDN1 Endothelin-1 COX2 Cyclooxygenase-2 VIT1 Vitiligo-associated protein 1